Histopatologi Tulang Daun Jeruk Siam (Citrus nobilis) yang Terinfeksi Penyakit Citrus Vein Phloem Degeneration (CVPD) Pada Tingkat Serangan Ringan, Sedang dan Berat - MUSLIM, MUSLIM; WIRAWAN, I GEDE PUTU; SRITAMIN, MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Histopatology Siamese Citrus Leaves (Citrus nobilis) Infected by Citrus Vein Phloem Degeneration (CVPD) at mild, moderate and severe attacks. Aims of this study is to identify the presence of the bacteria Liberobacter asiaticum, cause of CPVD (Citrus Vein Phloem Degeneration) disease and to know the differences in the histology of Siamese citrus plant tissue that is attacked by mild, moderate and severe attacks. This research was in the Laboratory of Plant Structure and Development of the Faculty of Biology, University of Gajah Mada and conducted at the UPT of the Genetic and Molecular Biology Laboratory of Udayana University. Field observations and sampling were carried out in the Wanasari Banjar, Kintamani Village, Kintamani Sub-District, Bangli District, Bali Province. There are several symptomatic citrus plants and attacked by CVPD with various levels of severity by visual appearance. On the observed land it were found that the attack percentage was 70% and the intensity of the attack was 46.4%. PCR (Poly polymeration chain reaction) identification method using OI1 and OI2 specific primers. The DNA band 1160 bp was found in mild, moderate, and severe chlorosis symptomatic samples. Leaves without symptoms do not change shape in the epidermis, cortex, xylem and phloem, while form changes occur in phloem, xylem and cortex in symptomatic citrus plants.